EDUKASI PERAWATAN JENAZAH DENGAN METODE DEMONSTRASI DALAM UPAYA PENINGKATAN PEMAHAMAN SYARIAT ISLAM - Sidqi, Moch. Hasan; Nurdiansah, Iszanul Dani; Bayhaqi, Hasmi Nur; Majid, Amir Bandar Abdul; El-Yunusi, M. Yusron Maulana (Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2024)
Caring for a corpse is an action that needs to be learned because in the Islamic religion it is obligatory if there is no one to carry it out. This community service aims to increase understanding about corpse care in theory and increase understanding about corpse care in practice at the Nurul Mushofa Islamic Boarding School, Tambak Lekok Village and Darun Najah MTs, Tampung Lekok Village, Pasuruan. Basic research on this service activity was carried out using the Participatory Action Research method. The results of this service show that students at the Nurul Mushofa Islamic Boarding School, Tambak Lekok Village and students at MTs Darun Najah, Tampung Lekok Village, Pasuruan have increased their understanding of theoretical and practical corpse care.